Does Time Interval from Thawing Multiple Straws of Semen to Insemination Affect Pregnancy Outcome of Lactating Dairy Cows? - J. Fehn; L. G. Mendonça (Kansas Agricultural Experiment Station Research Reports, 2019)
Technicians must follow guidelines when inseminating cows to avoid impacting the quality of semen and pregnancy per AI (P/AI). The interval from initiation of the thawing process of multiple semen straws until AI is an important aspect to be considered when evaluating the performance of AI technicians. Time interval from thawing to AI can be affected by the skill level of the AI technician, distance from the thawing unit to location of insemination, and labor efficiency. Because modern dairy farms are becoming larger, it is important to evaluate if the interval from thawing to AI is impacting P/AI in large herds. The objective of this study was to investigate whether time interval from handling of semen to AI affects pregnancy outcome of lactating dairy cows housed in a modern dairy farm. Most of the AI occurred within 10 minutes after initiation of the thawing process. Pregnancy outcome was not affected by sequence of AI or time interval from thawing until AI. Technicians responsible to inseminate cows in large dairy farms should strive to deposit semen in the reproductive tract within 10 minutes after starting the thawing process. If the AI technician thaws multiple straws of semen simultaneously, it is important to consider the efficiency of the technician to deposit semen after thawing, and temperature of the thawing unit.
Keywords: semen straws; thawing procedure; sequence of insemination; frozen semen